Influence of gouge thickness and grain size on permeability of macrofractured basalt. Issue 12 (14th December 2016) - Wang, G.; Mitchell, T. M.; Meredith, P. G.; Nara, Y.; Wu, Z.
Abstract: Fractures allow crystalline rocks to store and transport fluids, but fracture permeability can also be influenced significantly by the existence or absence of gouge and by stress history. To investigate these issues, we measured the water permeability of macrofractured basalt samples unfilled or infilled with gouge of different grain sizes and thicknesses as a function of hydrostatic stress and also under cyclic stress conditions. In all experiments, permeability decreased with increasing effective pressure, but unfilled fractures exhibited a much greater decrease than gouge‐filled fractures. Macrofractures filled with fine‐grained gouge had the lowest permeabilities and exhibited the smallest change with pressure. By contrast, the permeability changed significantly more in fractures filled with coarser‐grained gouge. During cyclic pressurization, permeability decreased with increasing cycle number until reaching a minimum value after a certain number of cycles. Permeability reduction in unfilled fractures is accommodated by both elastic and inelastic deformation of surface asperities, while measurements of the particle size distribution and compaction in gouge‐filled fractures indicate only inelastic compaction. In fine‐grained gouge this is accommodated by grain rearrangement, while in coarser‐grained gouge it is the result of both grain rearrangement and comminution. Overall, sample permeability is dominated by the gouge permeability, which decreases with increasing thickness and is also sensitive to the grain size and its distribution. Our results imply that there is a crossover depth in the crust below which the permeability of well‐mated fractures (e.g., joints) becomes lower than that of gouge‐filled fractures (e.g., shear faults). Key Points: Fracture permeability is dramatically reduced in the presence of fault gouge Variation of gouge thickness and grain size can lead to large changes in fracture permeability Pressure cycling causes reduction in fracture permeability due to grain packing and/or comminution of gouge particles